Prospective surveillance of healthcare-associated infections and patterns of antimicrobial resistance of pathogens in an Italian intensive care unit - Aida Bianco; Maria Simona Capano; Valentina Mascaro; Claudia Pileggi; Maria Pavia (Antimicrobial Resistance and Infection Control, 2018)
Abstract Background The study aimed to evaluate the distribution of healthcare-associated infections (HAIs), the incidence rates and device utilization ratio (DUR) of device-associated infections (DAIs), as well as the distribution and patterns of antimicrobial resistance of the responsible pathogens. Methods Eligible patients who were admitted to an adult Intensive Care Unit (ICU) from May 1, 2013 to December 31, 2016 were included in the surveillance. Demographics, intrinsic and extrinsic risk factors, information regarding infection and isolated pathogens with antibiogram results were collected. Results One thousand two hundred eighty-three patients were included in the surveillance. One hundred forty-seven HAIs were detected with a cumulative incidence of 9.2 per 100 patients 4-year period and an incidence rate of 17.4 per 1000 patient days. Fifty-six out of 1283 patients were affected by at least one episode of ICU-acquired pneumonia, and 72.7% of these were associated with intubation. ICU-acquired bloodstream infections (BSIs) occurred in 4.4% of patients and 89.5% were catheter-related. ICU-acquired urinary tract infections (UTIs) occurred in 1% of patients, with 84.6% of the episodes being associated with the use of an urinary catheter. The pattern of antimicrobial-resistance in the isolates showed, among the Gram-positive bacteria, that 66.6% and 16.6% of Staphylococcus epidermidis were oxacillin and teicoplanin resistant, respectively. Among the Gram-negative bacteria, carbapenem resistance was found in 91.6% of Acinetobacter baumannii and 28.5% of Klebsiella pneumoniae isolates. Conclusions The majority of HAIs in the ICU studied were associated with the use of invasive devices. Since a significant proportion of these HAIs are considered preventable, reinforcement of the evidence-based preventive procedures are needed.